NOTA SÔBRE OS NEMATÓIDES QUE ATACAM A SERINGUEIRA NO ESTADO DE SÃO PAULO - Martinez, Ângelo Artur; Lordello, Luiz Gonzaga E.; Lordello, Rubens R. A. (REVISTA DE AGRICULTURA, 2016)
NOTA SÔBRE OS NEMATÓIDES QUE ATACAM A SERINGUEIRA NO ESTADO DE SÃO PAULO